KEDUDUKAN SURAT KEPUTUSAN PENGANGKATAN ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH DALAM PELAKSANAAN PERJANJIAN KREDIT SEBAGAI OBJEK JAMINAN DI PT. BANK RIAU KEPRI CABANG UTAMA PEKANBARU - Galuh Dwi Nugroho; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Important role as a banking institution that has been mandated by the Banking Law that lending activities is the primary function of banks in carrying out their business activities. Furthermore, in the activities of borrowing money is going in the community that generally are often required for the delivery of collateral by the debtor to the creditor. PT. Bank Riau Riau Main Branch Pekanbaru receive credit for members of Parliament to use collateral SK DPRD (decree of appointment of the member Regional Parliament), the problems that arise if the SK DPRD can be qualified as rights of material that can be used as a security object.Formulation of the problem to be discussed in this thesis are: 1. Is the SK DPRD is a body that can become the object of legal guarantee? 2. How is the position of material rights of SK DPRD in the implementation of the credit agreement at PT. Bank Riau Kepri Main Branch Pekanbaru?This type of research is Empirical Juridical. The nature of this research is descriptive. This research was conducted at PT. Bank Riau Kepri Main Branch is located at Jalan Sudirman No. 377 Pekanbaru. The conclusion of this study. First, in terms of legal provisions concerning the legal guarantee of SK DPRD can not be categorized as an object in the object collateral. Second, SK DPRD in Position the implementation of the credit agreement by Bank Riau Kepri just as authentic documents that must be met by the debtor so that the banks can be fulfilled the principle of trust against the debtor to pay off his credit.Suggestions writer, should the bank require additional collateral, so that the bank gained a strong guarantee legally from debtors, banks also need to be more selective accept prospective borrowers to apply prudence and more in-depth analyzes of the prospective borrower so as to minimize the risk of loans.Keywords: Position SK DPRD- Credit- Collateral